El diseño cuantitativo una estrategia metodológica para el manejo de información cuantitativa (2006)
ABSTRACT: The objective of this Module is to present/display an investigation process that leans basically in a methodologic design of quantitative type that uses the technique of the social survey like basic technique and that uses as a statistical package for the processing of the collected, purified and validated data.